„LOVEN ER KUN FOR DE SMÅ FOLK“: Sandhedskommissioner og fremstillinger af (u)retfærdighed i nationsop bygningsprocessen i Østtimor - Nygaard-Christensen, Maj (Tidsskriftet Antropologi, 2008)
This article is based on fi eldwork conducted in Timor Leste in 2004-5 and an ongoing fi eldwork commenced in early 2007. It is inspired by the frequent references to justice – and particularly to injustice – in political debates, public protests and media reports during both fi eldworks. The article examines how approaches to justice represented by the two truth commissions, CAVR and CTF, relate to alternative notions of justice in the nation-building process. The study should further show how the early nationalist movement created an idea of “The People” as united by a sense of shared suffering, and their enjoined fi ght against injustices. This notion of a people bonded through an experience of injustice created big expectations that independence would deliver better times. The same can be said for the time of the “post-confl ict”; the context in which most truth commissions operate. The “post-confl ict” period proved to be problematic with its inherent promises of a break with a diffi cult past. The article sees truth commissions as institutionalised attempts to realise this desire towards a break with a violent past in favour of a brighter future. However, in Timor Leste, the present does not yet live up to expectations created towards justice and social change, and the article further examines how, as a result, new understandings of justice come into being after independence.